(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The skin is an organ that primarily responds to tactile stimuli and directly responds to emotional impulses. The practise of dermatology has a psychosomatic component. There has long been speculation that psychological issues may be related to skin conditions. Psychodermatology examines how the mind and skin interact. According to the link between skin conditions and mental illnesses, it is categorised into three categories. In each of the three categories-psychosomatic illnesses, dermatological problems resulting from primary and secondary psychiatric disorders-different dermatological conditions are reviewed in this article. Psychiatric problems and its associated dermatological issues, such as stress and depression, are discussed. This review aims to precisely present the connection between the skin and the mind from a dermatology perspective. Psychodermatological problems’ negative consequences on a person’s quality of life are underlined. Both dermatologic and mental therapy options call for a multidisciplinary approach.